Influence of Erythropoiesis-Stimulating Agents on HbA1c and Fructosamine in Patients with Haemodialysis - Rasche, Franz Maximilian; Ebert, Thomas; Beckmann, Julia; Busch, Volker; Barinka, Filip; Rasche, Wilma Gertrud; Lindner, Tom H.; Schneider, Jochen G.; Schiekofer, Stephan (Experimental and Clinical Endocrinology & Diabetes, 2017)
HbA1c is the most accepted laboratory parameter for the long term observation of glucose control. There is still much of a debate about the use of HbA1c as a metabolic indicator in diabetic patients (DM) on haemodialysis (HD) and erythropoiesis-stimulating agent (ESA) therapy because of the altered erythrocyte turn over in patients with chronic kidney disease and haemodialysis (CKD5D). In 102 CKD5 patients with and without diabetes mellitus, we examined the dose dependent variability in HbA1c and fructosamine levels under haemodialysis and treated with epoetin α (n=48) and a new generation agent with continuous stimulation of methoxy polyethylene glycol epoetin beta (C.E.R.A.; n=54). HbA1c levels were affected by therapy with ESA treatments. ESA dose was inversely correlated with HbA1c and an escalation of 10.000 IU per week induced an estimated decrease of HbA1c of 0.6 percent. In addition, the increase of reticulocyte number as a marker for erythropoiesis was significantly inversely correlated with the increase of ΔHbA1c. ESA treatments had no such effect on the alternative metabolic parameter fructosamine. When compared, both therapeutic agents had comparable success in attaining haemoglobin (Hb) target values. C.E.R.A. showed better correlation and was more effective over a longer dose interval. Our results show that HbA1c levels in patients should be carefully interpreted based on interfering factors. Nevertheless, HbA1c is currently the most consistent parameter for use ascertaining metabolic status of patients suffering from diabetes mellitus.
Keywords: HbA1c; fructosamine; haemodialysis; erythropoiesis-stimulating agents; C.E.R.A.; epoietin α